2015
DOI: 10.1007/s11248-015-9892-6
|View full text |Cite
|
Sign up to set email alerts
|

Transportability of confined field trial data from cultivation to import countries for environmental risk assessment of genetically modified crops

Abstract: Requirement of in-country confined field trials for genetically modified (GM) crops prior to unrestricted release is well-established among countries with domestic regulations for the cultivation approval of GM crops. However, the requirement of in-country confined field trials is not common in countries where the scope of the application does not include cultivation. Nonetheless, Japan and China request in-country confined field trials for GM crops which are intended only for use as food, feed and processing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 20 publications
4
38
0
Order By: Relevance
“…Overall, results from these ERA studies are consistent with other studies previously done in other world regions (US EPA 2008; James 2014). Furthermore, additional results of field studies obtained from multiple geographies for GM soybean (Horak et al 2015) and GM maize (Nakai et al 2015; Ahmad et al 2016) demonstrate the utility of relevant data transportable across regions for the ERA of GM crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, results from these ERA studies are consistent with other studies previously done in other world regions (US EPA 2008; James 2014). Furthermore, additional results of field studies obtained from multiple geographies for GM soybean (Horak et al 2015) and GM maize (Nakai et al 2015; Ahmad et al 2016) demonstrate the utility of relevant data transportable across regions for the ERA of GM crops.…”
Section: Discussionmentioning
confidence: 99%
“…In-country data requirements by the Mexican regulatory system are of a confirmatory nature, given that the standard process to demonstrate crop safety for any commercial GM crop includes a stringent battery of rigorous scientific evaluations and independent regulatory reviews by most grain-importing and cultivating countries (Nakai et al 2015). By the time a GM crop product is introduced into the Mexican regulatory system, extensive evaluation has already taken place in other world areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For environmental risk assessments (ERA), the potential risks to biodiversity in Japan are evaluated for competitiveness, production of harmful substances and outcrossing ability based on the nature of the crop and the identity of transgenes and their gene products (MOF et al, 2003). For most of the cases, although environmental safety and agronomic characteristics are thoroughly studied for years at multiple locations in the countries where the GM crop is developed and/or the commercial cultivation is intended (Nakai et al, 2015), data collected from an in-country field trial is one of the requirements for the ERA to demonstrate the behavior within the environment of Japan (MAFF and MOE, 2014). Since the Cartagena Protocol Domestic Law was implemented in 2004, seven GM cotton lines have been approved to date that require conducting incountry field trials in Japan (Japan Biosafety Clearing House: http://www.biodic.go.jp/bch/ index.html).…”
Section: Introductionmentioning
confidence: 99%
“…The extrapolation of results from lower-tiered studies to inform risk assessments that consider the potential for field effects is well supported in the Bt literature, where meta-analyses examining correlation of laboratory and field data concluded that laboratory results generally predict (Duan et al, 2009) or over-estimate field effects (Naranjo, 2009). Building on the lessons from empirical testing and the evolution of risk assessment for GM crops (Dutton et al, 2003;Garcia-Alonso et al, 2006;Raybould, 2006;Rose, 2007;Romeis et al, 2011Romeis et al, , 2013Romeis et al, , 2014Carstens et al, 2014), the risk assessment community recognized that surrogate organism testing (Carstens et al, 2014) and data transportability (Nakai et al, 2015), when appropriately applied (Paula et al, 2016), provide high value through informing and simplifying risk assessments performed across geographies in which the same crop is cultivated (Wach et al, 2016 . Event DAS-81419-2 combines two Bt proteins in soybeans to provide South American agricultural producers with wide-spectrum protection from feeding damage by certain key lepidopteran pests (Marques et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%